Innate immunity is linked to the severity of stable coronary artery disease through sCD40L pathway. (25th November 2020) - Silva, T.P.D; Napoleao, P; Pinheiro, T; Selas, M; Silva, F; Ferreira, V; Goncalves, A; Reis, J; Castelo, A; Bras, P; Cruz Ferreira, R; Mota Carmo, M
Abstract: Introduction: Soluble CD40 ligand (sCD40L) activates different cell types involved in innate immunity, including macrophages and platelets. The influence of innate immunity, particularly of sCD40L pathway, on stable coronary artery disease (SCAD) expression is not fully understood. We evaluated if sCD40L expression is related to the presence of SCAD and to its clinical and anatomical severity. Methods: We prospectively recruited two groups of age- and sex-matched participants: 1) without coronary artery disease (CAD) (calcium score=0, no soft plaques on coronary angioCT scan) (controls); and 2) with stable obstructive CAD (≥50% for the left main, ≥70% for other epicardial vessels, on invasive coronary angiography). Acute atherosclerotic events or coronary artery bypass grafting (CABG) within 12 months, previous percutaneous coronary intervention, heart failure, infection, malignancy and severe renal dysfunction were exclusion criteria. Clinical, laboratorial and anatomical data were prospectively collected. Serum was stored at −80°C and measurements were performed in a blinded fashion, by ELISA (sCD40L Human Quantikine). Results: Sixty-three participants were included: 14 controls and 49 patients with SCAD. In SCAD patients, classical cardiovascular risk factors were globally more prevalent and the serum levels of sCD40L (5553±3356 vs 3099±644 ng/mL, p<0.001), leucocytes counts (7.6±1.8 vs 6.4±1.7x10 9 /L, p=0.010), neutrophils counts (4.4±1.5 vs 3.5±1.5x10 9 /L, p=0.010) and neutrophils/lymphocytes ratio (2.4±1.1 vs 1.9±0.7, p=0.019) were significantly higher, while c-reactive protein (CRP) levels did not differ, compared to controls. sCD40L levels were positively correlated with leucocytes (r=0.36) and neutrophils (r=0.28) counts (all p<0.05), but not with CRP. Clinically, sCD40L levels were associated (ANOVA p<0.001) and positively correlated (Pearson r=0.54, p<0.001) with angina severity (Fig. 1A). Anatomically, patients with a higher number of significant coronary artery lesions presented higher sCD40L levels (Fig. 1B); sCD40L levels were positively correlated with the number of: diseased vessels (r=0.33), significant coronary artery lesions (r=0.31), and all coronary artery lesions (r=0.33) (all p<0.05), without correlation with the Gensini score. Linear regression analysis considering clinical and laboratorial data revealed that sCD40L was an independent predictor of CAD severity, as assessed by the number of significant lesions (model: sCD40L β 0.28, 95% CI 0.03–0.34; hypertension β 1.1, 95% CI 0.97–3.64). Among SCAD patients, those with previous CABG (n=15) had lower sCD40L levels than patients waiting for revascularization (n=34) (3317±1680 vs 6793±3631 ng/mL, p<0.001). Conclusions: Increased expression of sCD40L was associated with the presence of SCAD, with angina severity and with CAD severity, while previous revascularization was associated with decreased sCD40L levels. Funding Acknowledgement: Type of funding source: None